A review of Omadius Laporte de Castelnau, 1836 (Coleoptera: Cleridae) from Mêdog, Xizang, China, with descriptions of three new species - Yang, Gan-Yan (Zootaxa, 2026)
Five species of Omadius are reported from Mêdog, Xizang, China. Three are described as new: Omadius bii sp. nov.; O. medogensis sp. nov.; and, O. changchini sp. nov. In addition, O. parviceps (Gorham, 1892) is newly recorded from China. Two names are placed in synonymy with O. zebratus (Westwood, 1852): O. apicicornis Pic, 1927 syn. nov.; and O. alishanus Nakane, 1996 syn. nov. Furthermore, O. chapaensis Pic, 1927 syn. nov. is synonymized with O. parviceps, and O. pectoralis Schenkling, 1912 sp. reinst. is removed from synonymy with O. tricinctus Gorham, 1892. An identification key and illustrations of habitus, male terminalia, and other diagnostic features are provided. This review will be valuable for future faunal studies on Omadius in China and the Himalaya.